2013
DOI: 10.1007/s10557-013-6473-x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II Type 2 Receptor (AT2R) is Associated with Increased Tolerance of the Hyperthyroid Heart to Ischemia-Reperfusion

Abstract: AT2R plays a significant role in T3-induced cardioprotection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
14

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
1
7
0
14
Order By: Relevance
“…This effect was associated with increased intracellular Ca 2+ level, which subsequently increased contractility and enhanced energy demands. It is well established that AMPK acts as a fuel gauge for the cell, thus it is also an important regulator of myocardial energy metabolism by promoting glucose uptake and glycolysis as well as fatty acid oxidation [50]. Our research confirms that prolonged T 3 treatment has the ability to alter the phosphorylation status of AMP kinase in myocardium, tissue with high-oxidative capacity.…”
Section: Discussionsupporting
confidence: 82%
“…This effect was associated with increased intracellular Ca 2+ level, which subsequently increased contractility and enhanced energy demands. It is well established that AMPK acts as a fuel gauge for the cell, thus it is also an important regulator of myocardial energy metabolism by promoting glucose uptake and glycolysis as well as fatty acid oxidation [50]. Our research confirms that prolonged T 3 treatment has the ability to alter the phosphorylation status of AMP kinase in myocardium, tissue with high-oxidative capacity.…”
Section: Discussionsupporting
confidence: 82%
“…The ascending aorta was cannulated to attach the heart to a non-recirculating water-jacketed, constant flow Langendorff apparatus (Radnotti; Harvard Apparatus USA). Hearts were perfused with a Kreb-Henseleit buffer (pH 7.4) aerated with a mixture of 95% O 2 -5% CO2 [14] . A saline filled latex balloon connected to a pressure transducer (Ad Instruments, MLT0380, Australia) was inserted into the left ventricle through an incision in the left atrial appendage.…”
Section: Ex-vivo Cardiac Contractility Assessmentmentioning
confidence: 99%
“…AT2R-dependent cell signaling and effects are less studied than those of the AT1R [138,139], but has vasodilation, anti-proliferative and anti-inflammatory effects [140,141]. Moreover, recent studies showed that AT2R regulates BP, cardiac hypertrophy and fibrosis, and cell death after MI [142,143]. Such effects could be mediated by increased production of NO and vasodilation [144][145][146].…”
Section: Angiotensin Type 2 Receptor (At2r)mentioning
confidence: 99%